Scenarios to Manage the Demand for N95 Respirators for Healthcare Workers During the COVID-19 Pandemic - Sun Y; Otomaru H; Quaye SED; Somani J; Bagdasarian N; Beh DLL; Fisher DA; Cook AR; Dickens BL (Dove Medical Press, 2020)
Yinxiaohe Sun,1 Hirono Otomaru,1,2,* Sharon Esi Duoduwa Quaye,1 Jyoti Somani,3 Natasha Bagdasarian,3 Darius LL Beh,3 Dale A Fisher,3,4 Alex R Cook,1 Borame L Dickens1,* 1Saw Swee Hock School of Public Health, National University of Singapore and National University Health System, Singapore; 2Department of Virology, Tohoku University Graduate School of Medicine, Sendai, Japan; 3Division of Infectious Diseases, National University Hospital, Singapore; 4Yong Loo Lin School of Medicine, National University of Singapore, Singapore, Singapore*These authors contributed equally to this workCorrespondence: Hirono Otomaru Email otomaruh@med.tohoku.ac.jpBackground: By estimating N95 respirator demand based on simulated epidemics, we aim to assist planning efforts requiring estimations of respirator demand for the healthcare system to continue operating safely in the coming months.Methods: We assess respiratory needs over the course of mild, moderate and severe epidemic scenarios within Singapore as a case study using a transmission dynamic model. The number of respirators required within the respiratory isolation wards and intensive care units was estimated over the course of the epidemic. We also considered single-use, extended-use and prolonged-use strategies for N95 respirators for use by healthcare workers treating suspected but negative (misclassified) or confirmed COVID-19 patients.Results: Depending on the confirmed to misclassified case ratio, from 1:0 to 1:10, a range of 117.1 million to 1.1 billion masks are required for single-use. This decreases to 71.6– 784.4 million for extended-use and 12.8– 148.2 million for prolonged-use, representing a 31.8– 38.9% and 86.5– 89.1% reduction, respectively.Conclusion: An extended-use policy should be considered when short-term supply chains are strained but planning measures are in place to ensure long-term availability. With severe shortage expectations from a severe epidemic, as some European countries have experienced, prolonged use is necessary to prolong supply.Keywords: COVID-19 pandemic, mathematical modelling, policy, healthcare resources, N95 respirators